Support to Sustainable Development Goal No.2 - Zero Hunger: A Study from Animal Feed Sub Sector Industries - Michelle, Vanessa; Gunawan , Juniati (PT ARRUS Intelektual Indonesia, 2023)
The study aims to analyze the disclosure of zero hunger SDGs in each sub-sector of livestock feed that has been listed on the Indonesian Stock Exchange. Indonesia is currently lacking to meet its food needs with only 21.6% supplies. The zero-hunger SDGs are aimed in eliminating the problem of hunger. One of the company's types of industries that can help achieve the goals of the zero-hunger SDGs is the livestock feed sub-sector, which produce high protein food levels, such as eggs, chickens, milk, and some foods from agriculture. This research is descriptive methods based on content analysis. The samples applied from four subsector livestock feed companies registered with the BEI in 2015–2022 (population), with the total sample 32 data analysis. The information was analyzed from sustainability reports, financial reports, and the company's website from 2015 to 2022. The research shows that almost all companies were at 33–48% (medium disclosure), which means that the feed subsector has not optimally supported SDGS zero hunger against 11 indicators on each report, especially on the information of stunting reduction. There are three information among 11 disclosures which are disclosed mostly by the animal feed sub sector industries, namely (1) the implementation of production techniques and technology; (2) ensuring animals generate high-quality; (3) sustainably produced food. This information is related to nutritional problems, like stunting. In contrast, there are two pieces of information which have been least disclosed, including the establishment of an area, and the size of a sustainable area.